Secondary traumatic stress among midwifery students - BAYRI BİNGÖL, FADİME; DEMİRGÖZ BAL, MELTEM (WILEY, 2021)
Purpose This study aimed to examine the factors affecting secondary traumatic stress on midwifery students. Design and Methods This descriptive study was conducted between November and December 2018. Data were collected using information form and the Secondary Traumatic Stress Scale. Findings The study found that 22.2% of midwifery students met all the trauma criteria for posttraumatic stress disorder according to the Secondary Traumatic Stress Scale. Midwifery students who were unhappy to continue their education and those who wished to switch to another profession after graduation respectively showed a 2.8- and a 4-fold higher risk of meeting the trauma criteria (p < 0.05). Conclusion The secondary traumatic stress rate in midwifery students is particularly high considering the fact that one in five students fulfills all of the Secondary Traumatic Stress criteria. However, to reduce their secondary traumatic stress rate, students should be thoroughly assessed by the educators who could provide the support necessary. Implications for nursing practice: Before graduation from the midwifery departments, students traumatic stress symptoms could be assessed mental health nursing courses, which might enable to change their attitudes towards to cope with this situation. Especially after traumatic childbirths, midwifery students should be supported by mental health nurses to cope with traumatic stress. Midwifery students should be encouraged each and every possible moment to express their feelings when they experience traumatic stress and thus their skills for effective coping can be reinforced.
Keywords: midwifery student; posttraumatic stress disorder; psychological trauma; secondary traumatic stress; POSTTRAUMATIC-STRESS; MIDWIVES EXPERIENCES; MIXED-METHODS; BIRTH TRAUMA; EVENTS; EXPOSURE; CARE; PREVALENCE; SYMPTOMS; INTERVENTIONS